Incidence and determinants of low birth weight in a tertiary hospital at South Andaman: a prospective study - Stephen, Lena Charlette; Barik, Shreya; Malakar, Abhishek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Birth weight is an important predictor of an individual’s survival and well-being and the complications of children born with low birth weight (LBW) continue till adulthood. The incidence and risk factors of LBW are not known in the Andaman and Nicobar Islands and research answers can help institute appropriate preventive measures. The aim of the study was to determine the proportion of LBW due to intrauterine growth restriction (IUGR) and preterm birth (PTB) and its association with selected factors. Methods: The prospective study was conducted in Andaman and Nicobar Islands Institute of Medical Sciences amongst pregnant women admitted between January-June 2021. Women<18 years, with gestational age<28 weeks, and belonging to tribal groups were excluded. After delivery, birth-weight was recorded to the nearest 10 g in first hour. Results: The incidence of LBW was 24% with 57% due to IUGR. It was significantly higher in recent immigrants, gravidity beyond three, smokeless tobacco uses during pregnancy, high risk pregnancies including multiple miscarriages and preterm deliveries. Five or more antenatal check-ups and > 6 Kg weight gain during pregnancy were protective. Conclusions: Ensuring adequate antenatal check- ups and weight gain during pregnancy, control of tobacco exposure and quality care for women with recurrent abortions and high risk pregnancy is imperative, particularly targeting recent migrants. Strengthening ongoing family planning programmes to increase spacing, identifying pregnancies at risk of preterm deliveries and improved care of premature newborns should be a priority.